Electrolytes and batteries
By adding a first additive and a second additive to the electrolyte, the synergistic effect inhibits the dissolution of transition metals and the hydrolysis of Si-CH3 groups in the positive electrode active material of the battery, solving the problems of poor high-temperature cycle performance and gas expansion, and improving the high-temperature cycle performance and safety performance of the battery.
Patent Information
- Application Number
- CN202511274945.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-08
- Publication Date
- 2025-11-21
- Estimated Expiration
- 2045-09-08
AI Technical Summary
Existing electrolyte additives have problems such as high impedance, poor high-temperature cycle performance, and gas expansion in battery applications, which lead to the deterioration of battery cycle performance and safety performance.
An electrolyte containing a first additive and a second additive is used. The first additive inhibits the dissolution of transition metals in the positive electrode active material at high temperatures, while the second additive inhibits the gas generated by the hydrolysis of Si-CH3 groups. Through the synergistic effect of the two additives, the battery impedance and gas expansion are reduced.
It effectively improves the high-temperature cycle performance and safety performance of batteries, suppresses the dissolution of transition metals and gas production, and improves the overall performance of batteries.
Smart Images

Figure CN120784457B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of batteries, and particularly relates to an electrolyte and a battery. BACKGROUND
[0002] With the rapid development of markets such as pure electric vehicles, smart homes, electric tools, and intelligent transportation, consumers' requirements for the performance of batteries are continuously increasing. Lithium ion batteries are widely used in consumer electronics and energy storage and power batteries due to their high specific energy, long cycle life, and small self-discharge.
[0003] Currently, the performance of batteries is improved by adding electrolyte additives to the electrolyte. However, the current electrolyte additives still have problems such as high impedance, poor high-temperature cycle performance, and gas expansion in the actual battery application process, which leads to the cycle performance, rate performance, and safety performance of the deteriorated battery. Therefore, it is urgent to develop an electrolyte that can improve the high-temperature cycle performance of the battery, reduce the impedance of the battery, and inhibit the gas expansion of the battery. SUMMARY
[0004] The present application aims to at least partially solve one of the technical problems in the related art. To this end, the present application proposes an electrolyte, a battery, and a power device. The application of the electrolyte of the present application to the battery can effectively improve the cycle performance of the battery, reduce the impedance of the battery, and inhibit the gas expansion of the battery.
[0005] In a first aspect, the present application provides an electrolyte, comprising a first additive represented by Formula I and a second additive represented by Formula II,
[0006] Formula I, Formula II,
[0007] In Formula I, R1, R2, and R3 are each independently selected from H, F, C1-C4 alkyl, C1-C4 fluoroalkyl, C2-C4 alkenyl, C2-C4 fluoroalkenyl, C2-C4 alkynyl, C2-C4 fluoroalkynyl, C5-C7 cycloalkyl, phenyl, R4-substituted phenyl, and R5-substituted benzyl;
[0008] R4 and R5 are each independently selected from F, C1-C4 alkyl, C2-C4 alkenyl, C2-C4 alkynyl, C1-C4 fluoroalkyl, C2-C4 fluoroalkenyl, and C2-C4 fluoroalkynyl.
[0009] The first additive in the electrolyte can inhibit the dissolution of transition metals in the positive active material of the battery at high temperature, thereby avoiding adverse phenomena such as loss of active sites of the positive active material, but the battery storage at high temperature is prone to gas production, and the second additive can inhibit the hydrolysis of Si-CH3 groups in the electrolyte to produce carbon dioxide, ethylene and other gases, thereby improving the battery gas expansion problem. Therefore, the first additive and the second additive synergistically help to reduce the battery impedance at high temperature, inhibit the battery gas expansion, and at the same time improve the high-temperature cycle performance of the battery.
[0010] In addition, the electrolyte according to the above embodiments of the present application can also have the following additional technical features:
[0011] In some embodiments, R1, R2, R3 are each independently selected from F, C1-C4 alkyl, C1-C4 fluoroalkyl, C2-C4 alkenyl, C2-C4 fluoroalkenyl, C2-C4 alkynyl, C5-C7 cycloalkyl, phenyl, R4-substituted phenyl, and R5-substituted benzyl; R4 and R5 are each independently selected from F and C1-C4 alkyl.
[0012] In some embodiments, R1, R2, R3 are each independently selected from F, methyl, ethyl, n-propyl, i-propyl, t-butyl, cyclohexyl, ethenyl, phenyl, fluoro-phenyl, 3,4-butynyl, 2-trifluoromethyl-ethenyl, perfluoroethyl, and p-methylphenylmethyl.
[0013] In some embodiments, the first additive of formula I includes at least one of the following compounds:
[0014] Formula I-1, Formula I-2, Formula I-3, Formula I-4,
[0015] Formula I-5, Formula I-6, Formula I-7,
[0016] Formula I-8, Formula I-9, Formula I-10,
[0017] Formula I-11, Formula I-12, Formula I-13,
[0018] Formula I-14, Formula I-15, Formula I-16,
[0019] Formula I-17, Formula I-18, Formula I-19,
[0020] Formula I-20, Formula I-21, Formula I-22.
[0021] Therefore, it is helpful to further regulate the performance of the electrolyte by the selection of the group in the first additive.
[0022] In some embodiments, the mass percentage of the first additive is 0.1% to 2% based on the total mass of the electrolyte. Therefore, it is helpful to inhibit the dissolution of transition metal ions in the positive active material, reduce the loss of active lithium, and slow down the capacity decay of the battery.
[0023] In some embodiments, the mass percentage of the second additive is 0.1% to 2% based on the total mass of the electrolyte. Therefore, it is helpful to inhibit the hydrolysis of Si-CH3 groups in the electrolyte to produce gas, thereby further improving the safety performance of the battery.
[0024] In some embodiments, the mass ratio of the first additive to the second additive is 0.1 to 3.33:1. Within the above ratio range, the two additives are better matched, and the safety performance of the battery can be further improved.
[0025] In some embodiments, the electrolyte further comprises a solvent and an electrolyte lithium salt, and at least one of the following conditions is met:
[0026] The solvent comprises at least one of a carbonate solvent and a carboxylic acid ester solvent;
[0027] The electrolyte lithium salt comprises at least one of lithium hexafluorophosphate, lithium bisfluorosulfonylimide, lithium tetrafluoroborate, and lithium bis-trifluoromethanesulfonylimide;
[0028] The molar concentration of the electrolyte lithium salt in the electrolyte is 0.8 mol / L to 2 mol / L. Therefore, it is helpful to improve the electrical conductivity and electrochemical stability of the electrolyte, and in turn improve the overall performance of the battery.
[0029] In some embodiments, the solvent comprises at least one of vinyl carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, gamma-butyrolactone, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, ethyl propionate, propyl propionate, butyl propionate, and methyl trifluoroethyl carbonate. Therefore, it is helpful to improve the dispersion uniformity and ionic conductivity of the electrolyte.
[0030] In a second aspect, the present application provides a battery comprising the electrolyte as described above. The battery has excellent cycle performance, rate capability and safety performance. DETAILED DESCRIPTION
[0031] Embodiments of the present application are described in detail below. The embodiments described below are exemplary and are intended to explain the present application, and should not be understood as limiting the present application.
[0032] The present application is based on the following findings and recognitions of the inventors:
[0033] In the related art, the energy density of a battery can be effectively improved by increasing the specific capacity of the positive active material and the charging voltage of the battery. However, in actual use, it is found that when the energy density of the battery is improved in the above way, the high-temperature cycle performance and high-temperature storage performance of the battery are severely impaired. For example, when the positive active material is a high-nickel ternary active material (NCM), a lithium manganese iron phosphate active material (LMFP) or a lithium iron phosphate positive active material (LFP), the energy density of the battery can be significantly improved by increasing the content of nickel, manganese or iron in the positive active material. However, the increase in the content of nickel, manganese or iron leads to poor structural stability of the positive active material, an increase in irreversible phase transition during the charge and discharge cycle, and thus adverse phenomena such as transition metal dissolution and loss of active sites in the positive active material, thereby affecting the performance of the battery.
[0034] The inventors have conducted in-depth research and found that during the cycle of the battery, on the one hand, the transition metal ions dissolved in the positive active material will deposit on the surface of the negative electrode, causing the SEI (Solid Electrolyte Interface) film on the surface of the negative electrode to continuously decompose and regenerate, continuously consuming active lithium in the electrolyte. As a result, the SEI film on the surface of the negative electrode thickens, the electrolyte is consumed more, and the by-products produced block the lithium extraction channel, leading to increased polarization. On the other hand, the positive active material produces manganese / nickel / iron-deficient phases due to the dissolution of transition metal ions, thereby causing lattice distortion and a decrease in structural stability of the positive active material, hindering the diffusion of lithium ions during the subsequent charge and discharge process, and thus increasing the polarization of the battery and increasing the high-temperature cycle capacity loss. On the other hand, the amount of active lithium re-embedded into the positive active material continuously decreases, the amount of low-lithium-embedded negative active material in the negative electrode increases, and the degree of disorder on the surface of the negative active material increases, which also promotes the SEI film regeneration reaction. The dissolution of transition metal ions in the positive active material, the decomposition and regeneration of the SEI film on the surface of the negative electrode all promote the decomposition of the electrolyte, leading to severe transition metal ion dissolution, high-temperature cycle capacity decay and high-temperature storage gas production in lithium ion batteries during high-temperature cycling.
[0035] Based on the above research, the inventors have developed a new electrolyte, which can effectively improve the problems of transition metal dissolution in the positive active material, high gas production in high-temperature storage, and effectively improve the high-temperature cycle performance and safety performance of the battery when applied to the battery.
[0036] Therefore, the first aspect of the present application provides an electrolyte, which comprises a first additive represented by Formula I and a second additive represented by Formula II,
[0037] Formula I, Formula II,
[0038] In Formula I, R1, R2, and R3 are each independently selected from H, F, C1-C4 alkyl, C1-C4 fluoroalkyl, C2-C4 alkenyl, C2-C4 fluoroalkenyl, C2-C4 alkynyl, C2-C4 fluoroalkynyl, C5-C7 cycloalkyl, phenyl, R4-substituted phenyl, and R5-substituted benzyl.
[0039] R4 and R5 are each independently selected from F, C1-C4 alkyl, C2-C4 alkenyl, C2-C4 alkynyl, C1-C4 fluoroalkyl, C2-C4 fluoroalkenyl, and C2-C4 fluoroalkynyl.
[0040] The first additive in the electrolyte can inhibit the dissolution of transition metals in the positive active material of the battery at high temperature, thereby improving the adverse phenomena such as the loss of active sites of the positive active material. The main reason is that: on the one hand, the difluorophosphoric acid group (mainly P=O) in the first additive can coordinate with the transition metal ions (including but not limited to Mn 2+ / Fe 2+ / Co 2+) to form stable chelate, which can prevent transition metal ions from leaving the lattice into the electrolyte, thereby inhibiting the dissolution of transition metals; on the other hand, the first additive can produce interface passivation, and the Si-O-P containing composite CEI layer is generated on the surface of the positive electrode by oxidation, which physically blocks the direct contact of the electrolyte with the positive electrode active material, reduces the metal dissolution rate, and at the same time reduces the interface impedance. However, the addition of the first additive is easy to hydrolyze at high temperature and initiate chain reaction to aggravate the battery gas production. Specifically, one of the main reasons for battery storage gas production at high temperature (> 60℃) is that the Si-CH3 group in the electrolyte is easy to hydrolyze to generate CH3OH and SiO2 at high temperature (> 60℃), which initiates a series of reactions to produce CO2, CH4 and C2H4 gas, and the addition of the first additive also aggravates the gas production by hydrolysis reaction, and the content of HF in the electrolyte increases, the acidity of the electrolyte increases, which can further aggravate the dissolution of transition metals. By adding the second additive, the gas production of the battery at high temperature can be effectively inhibited. Specifically, the phenolic hydroxyl group (-OH) in the second additive can capture the free radicals (such as PF 5 ⁻, CO3 2 ⁻) produced by the decomposition of the electrolyte, block the chain reaction, and reduce the generation of CO2, CH4 and C2H4 gas; at the same time, the B-O bond contained in the second additive reacts with free HF to generate stable BF3·OH⁻ complex, reducing the acidity of the electrolyte (such as HF content < 50 ppm), thereby inhibiting the gas production by the side reaction of the electrolyte, and improving the dissolution of transition metals.
[0041] In addition, the Si-O-P group of the second additive and the first additive can form a Li-B-P-O composite CEI film on the surface of the positive electrode, improve the interface stability of the positive electrode active material at high temperature (60℃), and further inhibit the dissolution of transition metal ions in the positive electrode active material. However, the generation of B-O complex by adding the second additive may thicken the CEI layer, which increases the impedance; and the Si-F bond generated by the hydrolysis of the first additive (such as C3H9F2O2PSi) can react with the B-O bond of the second additive (LiBSc) to generate B-F bond, which can convert the phenolic hydroxyl group of the second additive (LiBSc) into more stable borofluorohydric acid to form an ultrathin composite CEI film, thereby avoiding the thickening of the CEI and the increase of the impedance.
[0042] Therefore, the synergistic effect of the first additive and the second additive can effectively inhibit the dissolution of transition metal ions at high temperature, reduce the impedance of the battery, and at the same time avoid the problem of large gas production during high temperature storage, effectively improve the high temperature cycle performance, safety performance and other performances of the battery.
[0043] As an example, the principle of battery gas production is as follows: the -Si(CH3)3 group in the molecule hydrolyzes at high temperature (> 60℃), generates CH3OH and initiates chain reaction:
[0044] C3H9F2O2PSi + H2O → CH3OH + (CH3)2Si(OH)F + ·CH3(radical)
[0045] ·CH3+ electrolyte → CO2 / C2H4(gas production).
[0046] In some embodiments, each of R1, R2, R3 in the first additive is independently selected from F, C1-C4 alkyl, C1-C4 fluoroalkyl, C2-C4 alkenyl, C2-C4 fluoroalkenyl, C2-C4 alkynyl, C5-C7 cycloalkyl, phenyl, R4-substituted phenyl, and R5-substituted benzyl; each of R4 and R5 is independently selected from F and C1-C4 alkyl. In this way, the first additive has better effect in inhibiting transition metal dissolution, and can further improve the overall performance of the battery.
[0047] In some embodiments, each of R1, R2, R3 is independently selected from F, methyl, ethyl, n-propyl, i-propyl, t-butyl, cyclohexyl, ethenyl, phenyl, fluoro-phenyl, 3,4-butynyl, 2-trifluoromethyl-ethenyl, perfluoroethyl, and p-methylphenylmethyl. In this way, the first additive has better effect in inhibiting transition metal dissolution, and can better synergize with the second additive, thereby further improving the overall performance of the battery.
[0048] Specifically, the first additive of formula I includes at least one of the following compounds:
[0049] Formula I-1, Formula I-2, Formula I-3, Formula I-4,
[0050] Formula I-5, Formula I-6, Formula I-7,
[0051] Formula I-8, Formula I-9, Formula I-10,
[0052] Formula I-11, Formula I-12, Formula I-13,
[0053] Formula I-14, Formula I-15, Formula I-16,
[0054] Formula I-17, Formula I-18, Formula I-19,
[0055] Formula I-20, Formula I-21, Formula I-22.
[0056] Therefore, the first additive has better effect on inhibiting transition metal dissolution, and can better synergize with the second additive, thereby further improving the comprehensive performance of the battery.
[0057] CAS No. of Formula I-1 is 2708941-25-5, CAS No. of Formula I-2 is 4419-25-9, CAS No. of Formula I-3 is 13683-39-1, CAS No. of Formula I-4 is 4414-27-1, CAS No. of Formula I-5 is 4414-26-0, CAS No. of Formula I-6 is 4480-02-8, CAS No. of Formula I-7 is 2577172-95-1, CAS No. of Formula I-8 is 13683-40-4, CAS No. of Formula I-9 is 2577172-93-9, CAS No. of Formula I-10 is 2708941-27-7, CAS No. of Formula I-11 is 2287283-36-5, CAS No. of Formula I-12 is 6231-57-8, CAS No. of Formula I-13 is 1386-54-9, CAS No. of Formula I-14 is 2708941-26-6, CAS No. of Formula I-15 is 6231-58-9, CAS No. of Formula I-16 is 6231-59-0, CAS No. of Formula I-17 is 2577172-94-0.
[0058] The synthesis method of Formula I-18 is as follows: under anhydrous condition, sodium difluorophosphate (moisture ≤20 ppm) is added to a reaction kettle, then ultradry acetonitrile solvent is added, the solid is dissolved by stirring at a temperature of 20-60°C, then tri-vinylchlorosilane (CAS No. 1871-21-2, moisture ≤20 ppm) is slowly added, a nitrogen atmosphere is maintained during the addition of tri-vinylchlorosilane and continuous stirring is maintained at 20-60°C for about 8h, wherein the molar ratio of sodium difluorophosphate, tri-vinylchlorosilane and acetonitrile solvent is 1:1:11, after the reaction is completed, it is placed at room temperature for about 2h, then the solid precipitate is removed by filtration, then the solvent and volatile by-products are removed by nitrogen bubbling, and Formula I-18 product is obtained.
[0059] The synthesis method of formula I-19, formula I-20, formula I-21, formula I-22 is the same as that of formula I-18 except that the raw materials are different. The raw materials for the synthesis of formula I-19, formula I-20, formula I-21, formula I-22 are dimethyl acetylenic butyl chlorosilane (CAS No. 2069196-19-4), dimethyl (trifluoroacetylenyl) chlorosilane (CAS No. 89705-02-2), tris (pentafluoroethyl) chlorosilane (CAS No. 1620665-21-5), and dimethyl (p-methyl benzyl) chlorosilane (CAS No. 1833-28-9).
[0060] In some embodiments, the CAS No. of the second additive shown in formula II is 161589-07-7.
[0061] In some embodiments, the electrolyte further comprises a solvent, and the solvent comprises at least one of a carbonate solvent and a carboxylic acid ester solvent, and specifically can comprise at least one of vinyl carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, γ-butyrolactone, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, ethyl propionate, propyl propionate, butyl propionate, and methyl trifluoroethyl carbonate. In other embodiments, the solvent can comprise at least two of vinyl carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, γ-butyrolactone, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, ethyl propionate, propyl propionate, butyl propionate, and methyl trifluoroethyl carbonate. In some embodiments, the solvent can comprise vinyl carbonate, ethyl methyl carbonate, and dimethyl carbonate in a mass ratio of 1: (0.5-2): (0.5-2). The above-mentioned solvents have high dielectric constants and can effectively dissolve lithium salts, thereby improving the electronic conductivity and dispersion uniformity of the electrolyte, and the use of the above-mentioned solvents can improve the cycle life, charge-discharge rate, high-temperature performance, low-temperature performance, and energy density of the battery.
[0062] In some embodiments, the electrolyte further comprises an electrolyte lithium salt, and specifically can comprise at least one of lithium hexafluorophosphate, lithium bisfluorosulfonylimide, lithium tetrafluoroborate, and lithium bis-trifluoromethanesulfonylimide. The above-mentioned electrolyte lithium salts have high conductivity and can quickly conduct lithium ions between the positive and negative electrodes, thereby improving the charge-discharge rate of the battery. At the same time, the above-mentioned electrolyte lithium salts have high stability and are not easy to decompose at high temperatures, which helps to improve the safety performance of the battery.
[0063] In some embodiments, the molar concentration of the electrolyte lithium salt in the electrolyte is 0.8 mol / L to 2 mol / L, and specifically, can be 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.9 mol / L, 2.0 mol / L, etc. The above molar concentration helps the electrolyte lithium salt to be fully dissolved, so that the electrolyte has high ionic conductivity and low manufacturing cost. At the same time, it can basically avoid the problems of too high molar concentration of the electrolyte lithium salt, which leads to too large viscosity of the electrolyte, affects ion transmission, and too low molar concentration of the electrolyte lithium salt, which leads to too low ionic conductivity of the electrolyte, slow charging and discharging, etc.
[0064] In some embodiments, the mass percentage of the first additive based on the total mass of the electrolyte is 0.1% to 2%, and specifically, can be 0.1%, 0.2%, 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, etc. The mass percentage of the first additive in the above range helps to inhibit the dissolution of transition metal ions in the positive active material. It can basically avoid the problems of too low mass percentage of the first additive, which leads to difficulty in forming a stable electrolyte SEI film, thereby leading to the problem of electrode exposure, and too high mass percentage of the first additive, which leads to exponential growth of hydrolysis side reactions (obvious increase in gas production), too large viscosity of the electrolyte, affects ion transmission and increases cost, etc.
[0065] In some embodiments, the mass percentage of the second additive based on the total mass of the electrolyte is 0.1% to 2%, and specifically, can be 0.1%, 0.2%, 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, etc. The mass percentage of the second additive in the above range helps to inhibit the generation of gas due to the hydrolysis of Si-CH3 groups in the electrolyte, thereby further improving the safety performance of the battery. At the same time, it can avoid the problems of too low mass fraction of the second additive, which leads to difficulty in fully removing free radicals and gas, and too high mass fraction of the second additive, which leads to deposition of B-O complex thickening CEI (increased impedance), reduction and consumption of Li + by salicylic acid ligand (cycle capacity attenuation), and too large viscosity of the electrolyte, affects ion transmission and increases cost, etc.
[0066] In some embodiments, the mass ratio of the first additive and the second additive is 0.1-3.33:1, specifically 0.1:1, 0.5:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.33:1, etc. Within the above ratio range, a dynamic balance of radical scavenging and hydrolysis inhibition and interface film synergistic construction can be achieved, covering the needs from transition metal dissolution prevention dominated to gas production prevention dominated, providing flexible adjustment space for industrialization, and the two additives have better coordination, which can further improve the safety performance of the battery. If the ratio is too small, the Si-O-P content in the CEI layer is insufficient, the metal dissolution inhibition effect is relatively not obvious, and at the same time, the second additive is excessive, which can cause the deposition of B-O complex to thicken the CEI (the impedance increases), and the reduction and consumption of salicylic acid ligand Li + If the ratio is too large, the second additive can not meet the demand of scavenging free radicals, which can cause the hydrolysis side reaction to grow exponentially (the gas production increases significantly).
[0067] Specifically, taking the first additive: second additive = 1:1 (i.e. 0.5%:0.5%) as an example, the synergistic effect of the two is explained in detail.
[0068] (1) Dynamic balance of radical scavenging and hydrolysis inhibition
[0069] According to the stoichiometric matching: the molar concentration of ·CH3 free radicals generated by the hydrolysis of the first additive is approximately 0.024 mol / L; the molar concentration of the hydroxyl group of the second additive is approximately 0.037 mol / L, which satisfies: [phenolic hydroxyl group]: [·CH3] ≈ 1.54:1, covering the demand for radical scavenging (the theoretical molar ratio needs to be >1:1). Therefore, the hydrolysis rate of the first additive and the radical scavenging ability of the second additive match to achieve a dynamic balance of radical scavenging and hydrolysis inhibition.
[0070] (2) Interface film synergistic construction
[0071] CEI layer composite structure: wherein the first additive provides a Si-O-P skeleton (high mechanical strength and low impedance), and the second additive is embedded in a B-O-B network (improving elasticity and repairing microcracks), and the two synergistically form a stable CEI film constructed by Si-O-B-P crosslinking, reducing the dissolution of transition metal ions, and at the same time, the Si / B molar ratio in the interface film construction is approximately 1:1, forming a high-conductivity composite CEI film.
[0072] In a second aspect of the present application, a battery is provided, comprising the aforementioned electrolyte. The battery has good high-temperature cycle performance and safety performance.
[0073] It can be understood that the specific type of the battery is not particularly limited, and can be a primary battery, a secondary battery; or can be a lithium ion battery. The shape of the battery can be a cylindrical battery, a square battery, or any other shaped battery, etc., and according to the classification of the outer packaging, the battery can be a hard shell battery, a soft package battery, etc.
[0074] In some embodiments, the battery can include a positive electrode sheet, a negative electrode sheet, and a separator film, etc., all of which are soaked in an electrolyte. During the charging and discharging process of the battery, active ions are embedded and extracted between the positive electrode sheet and the negative electrode sheet, and the electrolyte plays a role in conducting ions between the positive electrode sheet and the negative electrode sheet. The separator film is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent short circuit between the positive electrode sheet and the negative electrode sheet, while allowing the active ions to pass through. Thus, the battery has excellent high-temperature cycle performance and high-temperature storage performance.
[0075] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer located at least on one side of the positive electrode sheet, and the positive electrode active material layer includes a positive electrode active material.
[0076] In some embodiments, the positive electrode current collector can be a metal current collector or a composite current collector. For example, the metal current collector includes but is not limited to an aluminum foil current collector; the composite current collector can include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base material. The composite current collector can be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer material base material (such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0077] In some embodiments, the positive electrode active material of the lithium ion battery can include at least one of a layered structure positive electrode active material (such as nickel-cobalt-manganese ternary positive electrode material, nickel-cobalt-aluminum ternary positive electrode material, lithium / sodium nickelate, lithium / sodium cobaltate, lithium / sodium manganate, lithium / sodium-rich layered and rock salt phase layered materials), an olivine-type phosphate active material (such as lithium iron phosphate, lithium manganese phosphate, lithium manganese iron phosphate, etc.), a spinel structure positive electrode active material (such as spinel lithium manganate, spinel nickel-manganese lithium manganate, lithium-rich spinel lithium manganate and nickel-manganese lithium manganate, etc.). It can be understood that the above-mentioned positive electrode active material can further include a doping element and a coating layer, etc.
[0078] In some embodiments, the positive electrode active material can satisfy the general formula: Li a Ni b Co c M1 d M2 e O f Rg wherein, 1≤a≤1.2, 0.6<b<1, 0<c<1, 0<d<1, 0≤e≤0.2, b+c+d+e=1, 1≤f≤2, 0≤g≤1, f+g=2, M1may be Mn, Al, etc., M2may be Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W, Nb, etc., and Rmay be N, F, S, Cl, etc. In some other embodiments, the positive active material can also satisfy the general formula: LiFePO4. The above positive active material can further improve the gram capacity of the positive active material and reduce the cost of the positive active material.
[0079] In some embodiments, the binder in the positive active material layer can include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a vinylidene-fluoride-tetrafluoroethylene-propylene terpolymer, a vinylidene-fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, a tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorine-containing acrylic ester resin.
[0080] In some embodiments, the conductive agent in the positive active material layer can include at least one of super conductive carbon, conductive graphite, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0081] In some embodiments, the negative electrode sheet can include a negative current collector and a negative active material layer disposed on at least one side surface of the negative current collector.
[0082] As an example, the negative active material layer can include a negative active material, a thickening agent, a conductive agent, and a binder, wherein the negative current collector can be a metal foil, for example, the metal foil can be a copper foil.
[0083] According to embodiments of the present application, the negative active material can include a carbon-based material, a silicon-based material, a tin-based material, etc.
[0084] According to embodiments of the present application, the binder in the negative active material layer can include, but is not limited to, at least one of styrene butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0085] According to embodiments of the present application, the conductive agent in the negative active material layer can include, but is not limited to, at least one of super conductive carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0086] In some embodiments, the separator can employ a separator known in the art that can be used for lithium ion batteries and is stable to the electrolyte used, such as a polyethylene separator, a polypropylene separator, a polyethylene / polypropylene composite separator, and the like.
[0087] The present application is described below with reference to specific examples, which are merely illustrative and not limiting in any way. If a specific technique or condition is not mentioned in the examples, it is performed according to the technique or condition described in the literature or according to the product manual.
[0088] Example 1
[0089] Preparation of the positive electrode sheet: the positive electrode active material NCM811, the binder polyvinylidene fluoride (PVDF), the conductive agent carbon black, and the conductive agent carbon nanotube were mixed uniformly at a weight ratio of 93:2.3:2:0.7, N-methyl pyrrolidone (NMP) was added, and stirring was performed under the action of a vacuum stirrer until the mixed system became a positive electrode slurry with uniform fluidity; the positive electrode slurry was uniformly coated on the positive electrode current collector aluminum foil, and the coating amount was 35 g / m 2 After drying at 85°C, cold pressing, edge cutting, sheet cutting, and striping were performed, the strips were dried at 85°C under vacuum for 4 hours, and the tab was welded to obtain the positive electrode sheet.
[0090] Preparation of the negative electrode sheet: the negative electrode active material graphite, the conductive agent carbon black, the thickening agent sodium carboxymethyl cellulose (CMC-Na), and the binder styrene-butadiene rubber were mixed at a weight ratio of 95:1.5:1:2.5, deionized water was added, and a negative electrode slurry was obtained under the action of a vacuum stirrer; the negative electrode slurry was uniformly coated on the negative electrode current collector copper foil, and the coating amount was 20 g / m 2 After drying at 85°C, cold pressing was performed, edge cutting, sheet cutting, and striping were performed, the strips were dried at 85°C under vacuum for 4 hours, and the tab was welded to obtain the negative electrode sheet.
[0091] Preparation of the electrolyte: in an argon-filled glove box (moisture <10 ppm, oxygen <1 ppm), the solvents ethylene carbonate, methyl ethyl carbonate, and dimethyl carbonate were mixed uniformly at a mass ratio of 3:5:2, fully dried lithium bisfluorosulfonylimide was quickly added to the mixed solvent to make the molar concentration of lithium bisfluorosulfonylimide in the electrolyte 1 mol / L, and an electrolyte additive was added, and the electrolyte was obtained after being mixed uniformly. The mass fraction of the first additive (formula I-1) in the electrolyte was 0.5%, and the mass fraction of the second additive (formula II) in the electrolyte was 0.3%.
[0092] Preparation of the separator: a polyethylene separator with a thickness of 8 μm was selected.
[0093] Preparation of the lithium ion battery:
[0094] The positive electrode sheet, the negative electrode sheet and the separator film prepared according to the above process were subjected to a lamination process to form a lithium ion battery with a thickness of 4.7 mm, a width of 55 mm and a length of 60 mm, vacuum baked at 75°C for 10 hours, and injected with the electrolyte prepared as described above. After standing for 24 hours, the battery was placed in an environment at 45°C, and a pressure of 3 kg was applied. After charging to 4.0V at 0.1C (160 mA), the battery was allowed to stand for 2 days (to fully activate the battery) to obtain the battery.
[0095] The preparation process of the batteries of Examples 2-39 and Comparative Examples 1-2 was substantially the same as that of Example 1, and the specific parameters are shown in Table 1.
[0096] Performance test
[0097] The lithium ion batteries in Examples 1-39 and Comparative Examples 1-2 were subjected to high-temperature cycle performance tests, gas production after storage, and manganese transition metal elution after high-temperature cycling tests, and the test methods were as follows:
[0098] High-temperature cycle performance test: The battery was subjected to a cycle test at 45°C: the lithium ion battery was subjected to 500 charge-discharge cycles at a current of 1C, and the charge-discharge cut-off voltage was 2.5V-4.25V.
[0099] 500 cycle capacity retention rate (%) = (500th discharge capacity / 1st cycle discharge capacity) x 100%;
[0100] Drainage method for measuring gas production after storage: the storage condition was high-temperature storage at 45°C, and the storage time was 30 days. The gas production AV = (m1-m2) / p (m1 is the mass of the battery before storage, m2 is the mass of the battery after storage, and p is the density of liquid water);
[0101] Transition metal manganese elution: the battery after 500 high-temperature cycles was first discharged at a rate of 0.1C to the lower limit voltage of 2.5V, then disassembled to obtain the negative electrode sheet, and the negative electrode powder was scraped with a ceramic knife. The amount of transition metal ions in the negative electrode (i.e. the amount of transition metal eluted from the positive electrode and deposited on the negative electrode) was tested by ICP, which was the transition metal ion elution amount (ppm).
[0102] Table 1
[0103]
[0104] From the above test data, it can be seen that the use of two additives together can effectively inhibit the elution of transition metals and reduce gas production, thereby improving the cycle performance and service life of the battery.
[0105] In the description of the specification, the description using the terms "one embodiment", "some embodiments", "an example", "a specific example", or "some examples" etc. means that the particular feature, structure, material or characteristic being described is included in at least one embodiment or example of the present application. The illustrative appearances of the above-mentioned terms in various places in the specification are not necessarily referred to the same embodiment or example. Moreover, the particular features, structures, materials, or characteristics can be combined in any suitable manner in one or more embodiments or examples. Furthermore, the description herein of certain examples does not necessarily exclude these examples from the scope of the application, and these examples can be combined with each other for the purposes of one or more other examples.
[0106] Although the embodiments of the present application have been shown and described above, it is understood that the above-described embodiments are exemplary and are not to be interpreted as limiting the present application, and that variations, modifications, substitutions and changes can be made by those skilled in the art without departing from the scope of the present application.
Claims
1. An electrolyte, characterized by, The first additive of formula I and the second additive of formula II are included, Formula I, Formula II, In formula I, R1, R2, R3 are each independently selected from H, F, C1-C4 alkyl, C1-C4 fluoroalkyl, C2-C4 alkenyl, C2-C4 fluoroalkenyl, C2-C4 alkynyl, C2-C4 fluoroalkynyl, C5-C7 cycloalkyl, phenyl, R4-substituted phenyl and R5-substituted benzyl; R4 and R5 are each independently selected from F, C1-C4 alkyl, C2-C4 alkenyl, C2-C4 alkynyl, C1-C4 fluoroalkyl, C2-C4 fluoroalkenyl and C2-C4 fluoroalkynyl; The mass percentage of the first additive is 0.1% to 2% based on the total mass of the electrolyte; The mass percentage of the second additive is 0.1% to 2% based on the total mass of the electrolyte; The mass ratio of the first additive to the second additive is 0.1 to 3.33:
1.
2. The electrolyte according to claim 1, characterized in that, R1, R2, R3 are each independently selected from F, C1-C4 alkyl, C1-C4 fluoroalkyl, C2-C4 alkenyl, C2-C4 fluoroalkenyl, C2-C4 alkynyl, C5-C7 cycloalkyl, phenyl, R4-substituted phenyl and R5-substituted benzyl; R4 and R5 are each independently selected from F and C1-C4 alkyl.
3. The electrolyte of claim 1, wherein R1, R2, R3 are each independently selected from F, methyl, ethyl, n-propyl, isopropyl, tert-butyl, cyclohexyl, ethenyl, phenyl, fluorophenyl, 3,4-butynyl, 2-trifluoromethyl-ethenyl, perfluoroethyl and p-methylphenylmethyl.
4. The electrolyte of claim 1, wherein The first additive of formula I includes at least one of the following compounds: Formula I-1, Formula I-2, Formula I-3, Formula I-4, Formula I-5, Formula I-6, Formula I-7, Formula I-8, Formula I-9, Formula I-10, Formula I-11, Formula I-12, Formula I-13, Formula I-14, Formula I-15, Formula I-16, Formula I-17, Formula I-18, Formula I-19, Formula I-20, Formula I-21, Formula I-22.
5. The electrolyte of claim 1, wherein Further included are: The solvent and the electrolyte lithium salt satisfy at least one of the following conditions: The solvent includes at least one of a carbonate solvent and a carboxylic acid ester solvent; The electrolyte lithium salt includes at least one of lithium hexafluorophosphate, lithium bisfluorosulfonimide, lithium tetrafluoroborate and lithium bis-trifluoromethanesulfonimide; The molar concentration of the electrolyte lithium salt in the electrolyte is 0.8 mol / L to 2 mol / L.
6. The electrolyte of claim 5, wherein, The solvent includes at least one of vinyl carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, γ-butyrolactone, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, ethyl propionate, propyl propionate, butyl propionate and methyl trifluoroethyl carbonate.
7. A battery, characterized by The electrolyte of any one of claims 1-6 is included.
Citation Information
Patent Citations
Electrolyte system for preventing spinel lithium titanate radical lithium ion secondary battery from flatulence
CN102867990A
Electrolyte additive, electrolyte and battery
CN119674233A